Analisis Pengaruh Kemudahan Pengguna Terhadap Efektivitas Alat Kompresi Sampah Botol Plastik “Bottlepress” Berbasis IoT - Shinta Arafah Hidayanti; Nur Aziezah; Hikmah Rahmah; Walidatush Sholihah; Inna Novianty (International Forum of Researchers and Lecturers, 2024)
The purpose of this study was to determine the influence of users and the effectiveness of the Plastic Bottle Waste Compression Tool